Determination of minimal total harmonic distortion for single-phase multilevel inverter - Wong, Quan Ming; Sea, Yee Wei; Chew, Wei Tik; Yong, Wui Ven; Zaidi, Ahmad Firdaus Ahmad; Ahmad, Noor Syafawati; Ong, Siok Lan; Leong, Jenn Hwai (Institute of Advanced Engineering and Science, 2024)
Multilevel inverters (MLIs) offer numerous advantages, such as low voltage stresses on power switches, low switching losses, and high efficiency. Switching angles applied to MLI must be selected carefully to generate an output voltage waveform with low total harmonic distortion (THD). This paper proposes an improved algorithm to determine the switching angles with low THD for MLI. The proposed algorithm has been implemented using a MATLAB script to compute a set of switching angles with low THD from 3- to 31-level cascaded H-bridge MLI (CHBMLI). A PSIM simulation model has been developed to validate the switching angles and the corresponding THDs obtained from the MATLAB script. An experimental prototype has also been developed to validate the simulation results. The results obtained from the MATLAB script, the PSIM simulation, and the experimental measurement are in good agreement.